(untitled) (Global Journal of Science Frontier Research, 2013)
This paper describes method for modelling of helical-n-revolutional cyclical surfaces. The axis of the cyclical surface 1 is the helix s 1 created by revolving the point about n each other revolving axes o n (n = 1,2,3), that move together with Frenet-Serret moving trihedron along the cylindrical helix s. Particular evolutions are determined by its angular velocity and orientation. The moving circle along the helix s or s 1 , where its center lies on the helix and circle lies in the normal plane of the helix creates the cyclical surface.